Absenteeism-illness of education servers: profile of sick leaves in a federal institution - Figueiredo, Bárbara de Oliveira; Silva, Luiz Sérgio; Colodette, Renata Maria; Pereira, Luiza Possa; Silva, Larissa Bruna Bhering; Oliveira, Deíse Moura de; Moreira, Tiago Ricardo (Ciência e Natura, 2022)
Investigated the factors associated to the number of days of sick leave of federal civil servants in an educational institution and the values of their occupational indices in the period from 2014 to 2017. Data sociodemographic, occupational and sick leaves were obtained through documentary analysis of medical records and administrative systems. For analysis, we used the absolute and relative frequency and multiple linear regression. Calculated rate of absenteeism-illness, frequency index, severity index and the average duration of leaves, stratified by gender and job role. The sample of 5,115 events in the population of 1,104 servers confirmed the positive relationship between age of the server, the level of schooling of the role and mental and behavioral disorders with the largest number of days of leaves. The female gender, live in the city where works, servers those did not have information on the marital status, technical-administrative job role and the public service time proved to be associated with fewer days of leave. The results presented show the relevance of absenteeism-illness in the context of federal public education and indicate the needs of interference in this sector regarding the organization of work and the health-disease process of their servers.